Guest Editorial - van Dyk, Liezl (The South African Journal of Industrial Engineering, 2016)
“At least I know who I was when I got up this morning, but I think I must have been changed several times since then.” From “Alice’s Adventures in Wonderland & Through the Looking Glass” by Lewis Carroll This is one of the quotes by mathematician and logician, Charles L. Hodgson (better known by his pen name, Lewis Carroll) that inspired the theme and many conversations at the recent conference of the Southern African Institute for Industrial Engineering (SAIIE), held in Parys, North-West Province. Within a timespan of two months, three communities of concern to Industrial Engineering held their annual conferences in South Africa: the 27th annual conference of SAIIE (SAIIE27) (27-29 Oct 2016), the 45th annual conference of the Operations Research Society (ORSSA) (11-14 September 2016) and the 7th annual international conference of the Rapid Product Development Association of South Africa (RAPDASA) (2-4 November 2016) To promote the high quality of work delivered to these conferences and to encourage authors to present some of their best research, we introduced the Special Edition of the journal in which the best research presented at the abovementioned conferences would be published. I am honoured to be the guest editor for the special conference edition of this journal. The same double blind peer review process and criteria used for the journal were also used in this selection process, and the feedback from all reviewers was used to score submissions to create a shortlist. Each submission on the shortlist then underwent an additional round of review, where a senior peer reviewer confirmed the selection, and the editor of the journal confirmed the suitability. As a consequence, this special edition has a total of 25 articles, making this the edition with the most articles in the history of the journal. Of these 25 articles, sixteen originated from SAIIE27 out of a total of 68 peer reviewed papers, ORSSA contributed two articles out of 85 presentations and from RAPDASA, seven articles were selected out of 37. The identity and focus of the three respected communities that contributed to this edition are reflected by the papers contributed by each. However, overarching themes of concern for South African Industrial Engineers are mirrored in all the papers: energy and natural resource management; advanced information and manufacturing technology; decision support as well as new innovation and organizational paradigms and approaches, without neglecting the human factors: the well-being of employees and the experience of customers. For many authors this is the first time that their work is published in a full academic journal. I trust that this experience has provided them with the confidence and enthusiasm to keep on contributing to the knowledge base of Industrial Engineering. I hope that this will be an annual edition, taking research in Industrial Engineering and its associated disciplines forward. Liezl van Dyk Guest Editor and Programme Director: SAIIE 27